Stres dan Strategi Coping Remaja Pengguna Narkoba yang Menjalani Program Pasca Rehabilitasi di Badan Narkotika Nasional Provinsi Jawa Timur - Andyastanti, Tisnalia Merdya; Soedirham, Oedojo; Subarniati, Rika (Preventia: The Indonesian Journal of Public Health, 2022)
Drug abuse is a problem that must be taken seriously. Coping strategies are ways to deal with situations that are felt to be pressing and burden a person beyond their capabilities. The purpose of this study was to examine the coping strategies possessed by adolescent drug users who are currently undergoing a post-rehabilitation program at the National Narcotics Board (BNN) of East Java. The research method uses a qualitative method with a phenomenological approach. The sampling technique is similar to the purposive sampling technique. In-depth interviews were conducted with five adolescent informants who underwent post-rehabilitation programs at BNN East Java. The results obtained are the stress experienced by adolescents occurs because of family problems. These problems will be more complex in late adolescence, so that it requires coping strategies. The type of coping strategy used is an emotion focused coping strategy and problem focused coping. There is a need for early detection of stress and strengthening coping strategies for adolescent drug users to avoid relapse during rehabilitation and post-rehabilitation.